Ferulic acid reinstates mitochondrial dynamics through PGC1α expression modulation in 6‐hydroxydopamine lesioned rats. (27th October 2019) - Anis, Ehraz; Zafeer, Mohd Faraz; Firdaus, Fakiha; Islam, Shireen Naaz; Anees Khan, Azka; Ali, Asif; Hossain, M. Mobarak
Abstract : Disruption of the tightly regulated mitochondrial dynamics and energy homeostasis leads to oxidative stress and apoptotic cell death, as observed in neurodegenerative disorders such as Parkinson's disease (PD). Polyphenolic plant derivatives have been shown to alleviate such pathological features and have been used in models of neurodegenerative disorders in previous reports. In the current study, we utilized a 6‐hydroxydopamine (6‐OHDA) lesioned rat model of PD to explore the protective efficacy of polyphenolic phytochemical ferulic acid (FA) against mitochondrial dysfunction and explored its effect on gene and protein expression of mitochondrial dynamics regulators dynamin‐related protein 1 (Drp1)/mitofusin 2 (Mfn2) in lesioned animals. We also evaluated its effect on expression of mitochondrial biogenesis regulator PGC1α and apoptotic regulators BAX, cyt c, p53, and cleaved PARP. We found that oral FA supplementation alleviated 6‐OHDA induced oxidative stress, DNA fragmentation, morphological changes, and blocked apoptotic cascade. FA also reduced mitochondrial Drp1 expression and increased gene and protein expression of PGC1α, thereby regulating expression of its downstream target Mfn2 and restoring mitochondrial dynamics in lesioned animals. Our data suggest that targeting mitochondrial dynamics through modulation of PGC1α can prove to be a potent preventive strategy against PD pathology.